THE ROLE OF THE SUVAYSH CHANNEL IN INTERNATIONAL RELATIONS - Nurullayev Shavkat Muinovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The construction of the canal and its role in world trade and international relations.